Radio Communication for the Dissemination of Improved Livestock Production Technologies in Ethiopia - Wamatu, Jane; Zeleke, Muluken; Derseh, Anagaw; Ephrem, Nahom; Abiso, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The International Center for Agricultural Research in the Dry Areas (ICARDA) launched a pilot radio program to assess the potential of disseminating sheep fattening technologies to smallholder farmers using radio as a communication medium. The program was introduced in three pilot districts (Doyogena, Lemo, and Tembaro) of the Southern Nations, Nationalities, and Peoples' Region in July 2023. The target groups of the intervention were youths and women farmers who are involved or plan to engage in sheep fattening as a business. This mid-term review aims to provide initial insight about the progress made six months after the program rollout. Data collected from baseline and mid-term surveys were used to measure changes in relevant covariates. The baseline survey included 150 beneficiaries of the program, while the follow-up survey covered 60 participants recruited from the three pilot Districts. The mid-term evaluation shows that the radio program has been effective in communicating improved sheep-fattening technologies to the target population. Between the baseline and mid-term surveys, the proportion of individuals receiving information about improved technologies increased from 80% to 98%. Furthermore, during the mid-term review, over 90% of participants perceived that radio is a valuable or highly valuable medium for disseminating technological innovations to farmers relying on subsistence agriculture. This is a significant increase compared to the baseline and indicates that radio can be used effectively to disseminate innovative farming technologies to youth and women farmers. Although there were no improvements in the accumulation of livestock assets during the study period, average household income increased significantly by 4.7 times during the mid-term survey. The follow-up survey was conducted during the crop harvest season, and crop production is the primary source of income in the study area. Therefore, the main reason for the increase in income could be crop sales. However, part of the change in income could also be attributed to the expansion of business activities in livestock production after being beneficiaries of the radio program. In this regard, approximately 98% of the study participants stated in the mid-term review that they had benefited from participating in the radio program. The assessment also shows that about 32% of beneficiaries have not applied livestock production information to improve their livestock husbandry practices. This implies that the radio lessons need to incorporate topics related to the adaptation and use of modern livestock technologies, taking into account the socio-economic conditions of the study participants. One of the reasons for not adopting technologies could also be due to insufficient working capital. Therefore, to improve the application of improved technologies in livestock production, it is important to provide necessary support to youth and women facing resource constraints to enable them to adopt improved livestock technologies.